The Basic Understanding of Economic Crime - Reda Manthovani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2021)
Economic crimes are part of criminal law but have specificity. In Indonesia, the promulgation of economic crimes is relatively new because it has only become known since the promulgation of Emergency Law No. 7 of 1955 concerning Economic Crimes. The umbrella regulations for economic criminal law in Indonesia are contained in Law No. 7 of 1955 and other regulations governing the economic sector outside of Law No. 7 of 1955. The consequence is that the meaning of economic crimes can be divided into narrow meanings/ Limited and broad meaning. The term economic crime which is known in Indonesia when viewed from the substance of Law No. 7 of 1955 seems closer to or can be included in the term economic crime in a narrow sense. This is due to the fact that the law contains substantially only provisions governing a small part of overall economic activity. The development of science and technology has also given rise to business actors, which were previously carried out individually, but have developed in the form of business groups that join together in the form of corporations, both legal and non-legal entities. Clarke uses the term business crime. This term includes criminal acts related to and occurring in trading, financial, banking and taxation activities. Clarke has expanded the notion of business crime, namely an activity that (always) has the connotation of legitimate business and is not identical with the activities of a criminal syndicate. Economic crime is one of the forms and dimensions of the development of crime which is currently the center of attention and concern for the international community. This is proven by the many resolutions of the United Nations concerning this problem, for example one of the reports of the VIIth United Nations Congress reported that crime as a social problem arises due to economic factors.